Effects of Voice, Breath Studies and Art Therapy on Academic Motivation-Anxiety of Students - Unal Akbulut, Emine Ceylan; Yuceer Nishida, Ece Merve; Usen, Sebnem; Ucar, Emrah (HACETTEPE UNIV, 2025)
Sixty-three of the state university, faculty of education, and department of preschool education students who claimed to experience a lack of motivation and trait anxiety were included in an 8-week workshops within the scope of this study. 29 out of 63 students formed the experimental group; the remaining 34 were the control group. Students in the experimental groups formed; participated in one of the voice, breath workshops, or art therapy assigned to them online for 60 minutes per week. At the end of 8 weeks, the experimental groups were compared among themselves and with the control group; The extent to which they benefited from which workshop was measured with the Academic Motivation Scale developed by Vallerand et al. in 1989 and translated into Turkish by E. Yurt and E. N. Bozer in 2015, and it was investigated whether they would continue to apply what they learned in the project individually. Data were obtained from the Trait Anxiety Inventory, developed by Speilberger et al. in 1970 and translated into Turkish by Oner and Le Compte in 1985 due to validity and adaptation studies to Turkish culture. As a result of the study, the anxiety of 9 out of 10 participants in the Breath group consisting of those who received Breath workshop decreased. Their scores on the sub-dimensions of academic motivation remained the same. A decrease in the lack of motivation levels was observed in five participants in the Voice group, consisting of those who attended the Voice workshop. Their scores on other academic motivation sub-dimensions did not change.
Keywords: Voice workshop; breath workshop; art therapy; academic motivation; trait anxiety; Education & Educational Research